Arbutin improves lung injury in chicks induced by Mycoplasma gallisepticum infection - Zhiling Wan; Ting Liu; Anchun Cheng; Hui Li; Rutao Lin; Erpeng Zhu; Yao Huang; Shunxing Liu; Yu Tang; Chunlan Shan; Zhentao Cheng (Poultry Science, 2025)
Mycoplasma gallisepticum (MG) is a pathogen commonly found in poultry that can cause avian-associated respiratory diseases. Arbutin (AR) possesses various pharmacological activities, including anti-tumor, anti-inflammatory, apoptotic regulation, and anti-oxidative stress effects, however, its impact and mechanisms against inflammatory damage caused by MG infection remain unclear. The results demonstrated that after AR intervention, the MG-induced symptoms such as pulmonary wall thickening, lung tissue congestion and hemorrhage, inflammatory cell infiltration, and HD11 cell swelling were significantly ameliorated. Antioxidant activity increased, and the expression of KUL01 protein and transcription levels of chemokines in macrophages decreased significantly. MG infection activated the nuclear factor-κB (NF-κB)/nucleotide-binding oligomerization domain-like receptor protein 3 (NLRP3) signaling pathway in lung tissue, and AR intervention effectively regulated the expression of apoptosis genes, significantly inhibiting the transcription levels of NF-κB, NLRP3, Caspase-1, IL-1β, IL-18, and TNF-α genes within the pathway. The effect of AR on the NLRP3 target gene in MG infection was further confirmed through HD11 cell experiments. These results indicated that AR could reduce the damage caused by MG infection and effectively inhibit apoptosis, oxidative stress, and macrophage response induced by the infection, primarily through the regulation of the NF-κB/NLRP3 signaling pathway to protect the lung.